Chondroitinase-mediated degradation of rare 3-O-sulfated glucuronic acid in functional oversulfated chondroitin sulfate K and E - Fongmoon D. (2014)
Chondroitin sulfate K (CS-K) from king crab cartilage rich in rare 3-O-sulfated glucuronic acid (GlcUA(3S)) displayed neuritogenic activity and affinity toward various growth factors like CS-E from squid cartilage. CS-K-mediated neuritogenesis of mouse hippocampal neurons in culture was abolished by digestion with chondroitinase (CSase) ABC, indicating the possible involvement of GlcUA(3S). However, identification of GlcUA(3S) in CS chains by conventional high performance liquid chromatography has been hampered by its CSase ABC-mediated degradation. To investigate the degradation process, an authentic CS-E tetrasaccharide, Δ4,5HexUA-GalNAc(4S)-GlcUA(3S)- GalNAc(4S), was digested with CSase ABC, and the end product was identified as GalNAc(4S) by electrospray ionization mass spectrometry (ESI-MS). Putative GalNAc(6S) and GalNAc(4S,6S), derived presumably from GlcUA(3S)-GalNAc(6S) and GlcUA(3S)-GalNAc(4S,6S), respectively, were also detected by ESI-MS in the CSase ABC digest of a CS-E oligosaccharide fraction resistant to CSases AC-I and AC-II. Intermediates during the CSase ABC-mediated degradation of Δ4,5HexUA(3S)-GalNAc(4S) to GalNAc(4S) were identified through ESI-MS of a partial CSase ABC digest of a CS-K tetrasaccharide, GlcUA(3S)-GalNAc(4S)-GlcUA(3S)-GalNAc(4S), and the conceivable mechanism behind the degradation of the GlcUA(3S) moiety was elucidated. Although a fucose branch was also identified in CS-K, defucosylated CS-K exhibited greater neuritogenic activity than the native CS-K, excluding the possibility of the involvement of fucose in the activity. Rather, (3S)-containing disaccharides are likely involved. These findings will enable us to detect GlcUA(3S)-containing disaccharides in CS chains to better understand CS-mediated biological processes. © 2007 by The American Society for Biochemistry and Molecular Biology, Inc.